Effectiveness of Training of Software (Excel) for Bachelor Level (Bsc) Students in Birendra Multiple Campuses, Bharatpur (Nepalese Journal of Management Research, 2023)
This study aims to evaluate the knowledge levels on statistical software excel for the BSc 1st and 2nd year students in Birendra, Campus, Braratpur, Chitwan. Moreover the study also aims to examine the effectiveness of statistical software excel training for them. Out of 201 BSc physical group students in 1st and 2nd year, 52 students are taken as sample excluding nonresponses. To examine the knowledge about statistical software excel, 30 multiple choice questions had been asked to them before conducting training. 7 hours training for each (52) students had been conducted on statistical software excel. 15 days later from the end of training, the post-test has been done to them.The post-test average knowledge Score is (20.73±5.27) and pre-test score was (9.35±6.35). The finding of the difference of knowledge score has been satisfied the normality by exploratory data analysis with normal curve and Shapiro-Wilk normality test. The average score after training (total 52 students) is much greater than that of before training and the standard deviation after training is slightly lower. The t-test is statistically significant and the training is effective for BSc level students in Birendra Multiple campus, Bharatpur.